Pengaruh Infrastruktur, Investasi, Biaya Transportasi terhadap Jumlah UMKM dan Pertumbuhan Ekonomi Daerah yang Dilalui Tol Batang – Semarang. - Trisnawan, Yulius Langgeng; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 1 (2022): VOL 11 NO 1, JANUARI 2022 [1-403 ]DO - 10.24843/EEP.2022.v11.i01.p03, 2022)
Infrastructure is a country's needs that play a role in increasing business growth and economic growth. In infrastructure there are various kinds of economic variables such as investment and transportation costs. This creates an influence between interrelated variables. The purpose of this study was to examine the effect of infrastructure, investment, and transportation on the number of MSME and regional economic growth traversed by the Batang - Semarang Toll Road. This study uses a path analysis model with SPSS version 25, with secondary data retrieval through reports from BPJT, BUJT, and BPS. The results showed that infrastructure and investment had a positive and significant effect on the number of MSME, while costs had a negative and insignificant effect on the number of MSME. Infrastructure and the number of MSME have a positive and significant effect on economic growth, while transportation costs have a negative and insignificant effect on economic growth, and investment has no positive and significant effect on economic growth. Based on the results of the study, it can be said that the number of MSME mediates the variables of infrastructure, investment, and transportation costs on the economic growth of the area traversed by the Batang - Semarang Toll Road.